IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI DAN MANAJEMEN PERTANAHAN NASIONAL (SIMTANAS) TERHADAP PELAYANAN PUBLIK DI KANTOR PERTANAHAN KABUPATEN BADUNG - I Gusti Agung Ayu Yuliartika Dewi; Anak Agung Gede Oka Wisnumurti; I Made Sumada (Public Inspiration : Jurnal Administrasi Publik, 2017)
The purpose of this research is to find out the Implementation of the Policy of Information System and National Land Affairs Management (SIMTANAS) to public services in the Land Affairs Office of Badung Regency. The quality of the service given in the Land Affairs Office of Badung Regency has not yet maximum and there are still many complaints from the people. Based on the reality, the problem proposed are that how the Implementation of the Policy of Information System and National Land Affairs Management (SIMTANAS), and how effective and efficient of the implementation affect to the land affairs service quality in the Land Affairs Office of Badung Regency. In order to answer these problems, the research was qualitative research method with descriptive research type. The data obtained through observation and comprehend interview processes, secondary data and also utilizing documentary results. Informant selection was carried out by purposive sampling. Data analysis process was performed by using the Donald Van Meter and Carl Van Horn theories, categorizing and combining data that was obtained, and also determining some relevance correlations with those data. Data validation was carried out with triangulation of data source so data served are valid data. Result of this research shows that there has been improvement of land affairs service quality in Land Affairs Office of Badung Regency after implementing the SIMTANAS policy, although not yet maximal and it need system information and management development so that the land affairs service quality that given will enjoyed by all of the society.